Machine Learning Algorithm for Fault Detetction In Three Phase Power Systems - Porwal, Komal (International Journal of Computer Sciences and Engineering, 2023)
Machine learning (ML) finds extensive utility across diverse engineering domains, serving a myriad of purposes. Within the realm of power systems, traditional fault detection relies on relays and measurement equipment to pinpoint anomalies. These anomalies are subsequently categorized based on their characteristics. ML tools offer the prospect of crafting algorithms capable of forecasting these faults. This study entails the emulation of a power distribution system within software, employing machine learning algorithms to predict faults. The dependable and efficient operation of power systems stands as a pivotal factor in guaranteeing a constant power supply, thereby satisfying the requirements of contemporary society. Through the application of these methods, our aim is to create a more effective and precise fault detection algorithm tailored for three-phase power systems. This article delves into the intricacies linked with forecasting faults in power systems, provides an overview of pertinent ML methodologies, and delivers a case study that illustrates the efficacy of ML-driven intelligent fault prediction within real-world power system scenarios.